How do central bank projections and forward guidance influence private-sector forecasts? - Monica Jain; Christopher S. Sutherland (Bank of Canada, 2018)
We construct a 23-country panel data set to consider the effect of central bank projections and forward guidance on private-sector forecast disagreement. We find that central bank projections and forward guidance matter mainly for private-sector forecast disagreement surrounding upcoming policy rate decisions and matter less for private-sector macroeconomic forecasts. Further, neither central banks' provision of policy rate path projections nor their choice of policy rate assumption used in their macroeconomic projections appear to matter much for private-sector forecast disagreement.
Keywords: D83; E37; E52; E58; 330; Transmission of monetary policy; Central bank research; Inflation targets; Monetary policy; Monetary policy communications